TEACHING BIOLOGY THROUGH ACTIVE METHODOLOGIES: BUILDING A MANUAL TO INVESTIGATE THE INTERACTION BETWEEN POLLINATING PLANTS THROUGH THE PRODUCTION OF EXSICATAE - de Paula, José Ivyrson; Nadia, Tarcila Correia de Lima (Editora Impacto Científico, 2025)
This manual is the result of the research project "Teaching Biology through Active Methodologies: building a manual to investigate the interaction between plants and pollinators through the production of herbarium specimens," conducted by the Professional Master's Program in Biology Teaching (ProfBio) at the Federal University of Pernambuco's Vitória de Santo Antão campus. To construct this learning process, we propose innovation in teacher training through the implementation of active methodologies centered on youth empowerment and the stimulating and mediating role of teachers. We propose to investigate one of the most intriguing and questioning topics within the Biology curriculum: evolution. To this end, we studied the interaction between plants and pollinators, using herbarium specimens produced at the EREM Pastor José Florêncio Rodrigues school in Cabo de Santo Agostinho, Pernambuco.DOI: https://doi.org/10.56238/edimpacto2025.092-015